An early forest fire detection method based on unmanned aerial vehicle vision - Ma, Sha; Zhang, Youmin; Xin, Jing; Yi, Yingmin; Liu, Ding; Liu, Han (Chinese Control and Decision Conference, 2018)
Traditional forest fire detection methods based on flame are subject to detection delays due to the later appearrance of flame than smoke. When the flame is detected, the fire might have already been spread and out of control. Therefore, the objective of this paper is to study new fire detection method based on smoke. First a quadrotor unmanned aerial vehicle (UAV) is adopted to capture the fire video; then the collected video sequence will be processed by a series of preprocessing including filtering and image enhancement; finally a new significance detection algorithm is investigated for early and efficient smoke detection. Experimental results show that the algorithm can detect smoke effectively.